UMP, UoS organised A Symposium on Watershed Management - Aziman, Abdullah
Forty participants from Korea and Malaysia took part in an international symposium - 3rd Workshop Korea-Malaysia Symposium on Watershed Management for Sustainable Earth – that discussed about related technology in watershed management